RANCANG BANGUN HOTSPOT DAN MANAJEMEN PENGGUNA MENGGUNAKAN MIKROTIK DI PONDOK PESANTREN AL-ISMAILLIYUN - Vico Prabowo; Dani Anggoro; Arif Hidayat (Jurnal Mahasiswa Ilmu Komputer, 2026)
This study aims to design and implement a Mikrotik-based hotspot system with user management support, which is applied in educational environments such as schools or Islamic boarding schools. This system is built to facilitate structured internet access sharing, distinguishing between teacher, staff, and student users, and managing bandwidth to comply with established policies. The method used in this study is an experimental approach with stages of Mikrotik device configuration via Winbox, NAT, DHCP, DNS, firewall settings, and hotspot configuration. The implementation results show that the system can function well, marked by the successful user login process via user and password, bandwidth settings according to profiles (10 Mbps for teachers, 6 Mbps for staff, and 10 Mbps for students), as well as successful internet speed testing and stable network connections. In addition, the system is able to log in and monitor network usage in real-time. The conclusion of this study shows that the Mikrotik hotspot system is effective for use as a user-role-based network management solution in school environments. This research also opens opportunities for the development of OTP-based login features, as well as mobile dashboards to improve network management efficiency.